Full state feedback and feed forward control of servo smart window using MATLAB/Simulink - Rany Ayu Lestari; Unan Yusmaniar Oktiawati (Institute of Advanced Engineering and Science, 2022)
House as a place to carry out daily activities requires healthy air. The right step to improve air circulation is to use smart window. A control system method is needed so that smart windows can automate air circulation better. Temperature sensor will determine the minimum, maximum, and opening size of the smart window in order to perform the function of opening and closing effectively. Servo motors are used as actuators in the process of opening - closing windows. In this research, the full state feedback and feed forward control method are used to determine the best control theory for servo motor control for smart window systems. The motor control system modeling in smart window is designed by applying the previously studied control theory. Mathematical modeling was carried out to obtain system equations and performance index. The equation is then applied to the MATLAB/Simulink simulation so that the stability of the system can be monitored against disturbances in the form of noise originating from the sensor or the control system itself.